Abundance of Sesamia nonagrioides (Lef.) (Lepidoptera: Noctuidae) on the Edges of the Mediterranean Basin - Matilde Eizaguirre; Argyro A. Fantinou (Psyche: A Journal of Entomology)
Organisms inhabiting seasonal environments are able to synchronize their life cycles with seasonal cycles of biotic and abiotic factors. Diapause, a state of low metabolic activity and developmental arrest, is used by many insect species to cope with adverse conditions. Sesamia nonagrioides is a serious pest of corn in the Mediterranean regions and Central Africa. It is multivoltine, with two to four generations per year, that overwinters as mature larva in the northern of the Sahara desert. Our purpose was to compare the response of the S. nonagrioides populations occurring in the broader circum-Mediterranean area, with particular attention to the diapause period and the different numbers of generations per season. To this end, we tried to determine whether populations in the area differ in their response to photoperiod and whether we can foresee the number of generations in different areas. We present a model for predicting the occurrence of the critical photoperiod according to latitude and temperature and the spread of S. nonagrioides in the circum-Mediterranean countries. Responses of populations to short-day length suggest that the spread of the species is associated with a gradual loss of diapause in the southern areas, and that diapause incidence is positively correlated with latitude.